(untitled) (Práxis Educativa, 2024)
In this paper, which aims to honor Basil Bernstein in the year marking the centenary of his birth, special attention is given to the academic and personal relationship he maintained with the Estudos Sociológicos da Sala de Aula (ESSA) Group [Sociological Studies of the Classroom] at the University of Lisbon. Considering the fundamental investigation focus of this Group – Research in science education – the paper also highlights how Bernstein’s theory, particularly the theory of pedagogic discourse, intersected with this area, facilitating the attenuation of the traditionally existing boundaries between such distinct fields of knowledge. In the final section, as an example, empirical data from a study developed within the ESSA Group is presented to illustrate the aforementioned connection. Two distinct concepts from Bernstein’s theory – power and control – are employed, along with two sociological relationships that are essential for effective science learning: the relationship between teachers and students and the relationship between discourses. Keywords: Basil Bernstein. Science education. Pedagogic practice.